Autotitrating external positive end-expiratory airway pressure to abolish expiratory flow limitation during tidal breathing in patients with severe COPD: a physiological study. Issue 3 (10th September 2020) - Suh, Eui-Sik; Pompilio, Pasquale; Mandal, Swapna; Hill, Peter; Kaltsakas, Georgios; Murphy, Patrick B.; Romano, Robert; Moxham, John; Dellaca, Raffaele; Hart, Nicholas
Background: The optimal noninvasive application of external positive end-expiratory pressure (EPAP) to abolish tidal-breathing expiratory flow limitation (EFLT ) and minimise intrinsic positive end-expiratory pressure (PEEPi ) is challenging in COPD patients. We investigated whether auto-titrating EPAP, using the forced oscillation technique (FOT) to detect and abolish EFLT, would minimise PEEPi, work of breathing and neural respiratory drive (NRD) in patients with severe COPD. Methods: Patients with COPD with chronic respiratory failure underwent auto-titration of EPAP using a FOT-based algorithm that detected EFLT . Once optimal EPAP was identified, manual titration was performed to assess NRD (using diaphragm and parasternal intercostal muscle electromyography, EMGdi and EMGpara, respectively), transdiaphragmatic inspiratory pressure swings (Δ P di ), transdiaphragmatic pressure–time product (PTPdi ) and PEEPi, between EPAP levels 2 cmH2 O below to 3 cmH2 O above optimal EPAP. Results: Of 10 patients enrolled (age 65±6 years; male 60%; body mass index 27.6±7.2 kg.m −2 ; forced expiratory volume in 1 s 28.4±8.3% predicted), eight had EFLT, and optimal EPAP was 9 (range 4–13) cmH2 O. NRD was reduced from baseline EPAP at 1 cmH2 O below optimal EPAP on EMGdi and at optimal EPAP on EMGpara . In addition, at optimal EPAP, PEEPi (0.80±1.27 cmH2 O versus 1.95± 1.70 cmH2 O; p<0.05) was reduced compared with baseline. PTPdi (10.3±7.8 cmH2 O·s −1 versus 16.8±8.8 cmH2 O·s −1 ; p<0.05) and Δ P di (12.4±7.8 cmH2 O versus 18.2±5.1 cmH2 O; p<0.05) were reduced at optimal EPAP+1 cmH2 O compared with baseline. Conclusion: Autotitration of EPAP, using a FOT-based algorithm to abolish EFLT, minimises transdiaphragmatic pressure swings and NRD in patients with COPD and chronic respiratory failure. An automated ventilator algorithm, using the forced oscillation technique to detect tidal breathing expiratory flow limitation (EFLT ), identifies the optimum EPAP at which EFLT is abolished without causing unnecessary lung hyperinflation https://bit.ly/2WNyhWP